Large-restriction-fragment analysis of Mycobacterium kansasii genomic DNA and its application in molecular typing. - Iinuma, Y (1997)
Large-restriction-fragment (LRF) polymorphisms in Mycobacterium kansasii isolates from 84 patients with bronchopulmonary infections in Japan between the 1960s and 1995 were studied by pulsed-field gel electrophoresis (PFGE). Chromosomal fragments digested with VspI were most suitable for PFGE separation of 16 to 21 fragments of between 40 and 550 kbp. All 84 isolates and the type strain M. kansasii ATCC 12478 were successfully typed by LRF analysis with VspI digestion. Twenty-one distinctive LRF types were identified, and the LRF patterns tested over time were reproducible and stable. A computer-assisted dendrogram of the percent similarity demonstrated that isolates of 18 LRF types had relatively close genetic relatedness, while isolates of the remaining 3 types showed divergence. Sequence analysis of the 16S rRNA gene in the isolates showing divergent genetic relatedness revealed a sequence identical to that of a previously reported subspecies of M. kansasii. In the Chugoku district of Japan, 11 cases of M. kansasii infection which occurred in workers in a coastal industrial zone between 1982 and 1993 were caused by one particular strain tentatively named LRF type M. When both detailed demographic data for the patients and ecologic data for the M. kansasii isolates are obtained, LRF typing may be of potential use for investigating the source and transmission of M. kansasii infection.